Perikatan yang Lahir karena Kontrak dan Undang-Undang serta Hubungannya dengan Akta Autentik - Dongoran, Hana Marty; Aminah, Aminah (Al-Ishlah: Jurnal Ilmiah Hukum, 2023)
This study aims to delve deeper into the dynamics between obligations arising from contracts and laws and the role of authentic deeds, as well as to explore the implications of the legal force inherent in each element in establishing and maintaining an obligation. This study uses a normative legal research method. The collected legal material is then qualitatively analyzed to describe the problem and answer the study objectives. The results show that legal obligations can be formed through various mechanisms, including contracts, laws, and authentic deeds. A contract, which can be either a written or oral agreement, creates a legal bond between the parties, with its legal force depending on the fulfilment of established legality conditions. Laws, as regulations made by the government, establish rights and obligations that are generally applicable and binding for all citizens, including in the context of legal obligations. Meanwhile, an authentic deed created by a notary offers a higher level of legal certainty than ordinary contracts due to its inherent evidentiary power and legal recognition. Therefore, it is recommended that parties in an obligation carefully consider the type of agreement to use in line with the complexity and legal needs of the obligation. Written or oral contracts may suffice for simple transactions or agreements, which meet all required legality conditions. However, for more complex obligations or those requiring high legal certainty, such as property transactions or significant business agreements, it is highly advisable to use an authentic deed prepared and authenticated by a notary. Choosing the appropriate obligation mechanism will ensure the legality and legal force of the agreement and provide better protection for all involved parties against potential disputes in the future.